New species of Nuuanu (Amphipoda: Nuuanuidae) from Norfolk Island, Torres Strait and the Cocos (Keeling) Islands - Hughes, L. E.; Bopiah, A. (Zootaxa, 2013)
Three new species of Nuuanu, N. quintalana sp. nov., N. stuckeyorum sp. nov. and N. titaseyi sp. nov. are described from Norfolk Island, Tasman Sea; Cocos (Keeling) Islands, Indian Ocean and the Torres Strait, Australia, respectively. There are currently 17 described species of Nuuanu with the genus distributed world-wide.